Pemanfaatan Bunga Matahari Dengan Teknologi Fitoremediasi Untuk Pemulihan Lahan Bekas Tambang Timah di Bangka Belitung - Hisyam, Endang Setyawati; Putri, Adriyana; Karmini, Resti; Serly, Serly; Apriyanti, Yayuk (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2024)
Post-mining due to mining activities will produce heavy metals in the form of acidic water and accumulate in the land. The poor quality of the land used by tin mining causes damage to the land ecosystem so that the land cannot be regrown by vegetation and the Pb (Lead) content in tin tailings is 6.29 ppm. The aim of this research is land restoration, namely carrying out revegetation using sunflower plants to absorb the heavy metal Pb with the concept of edutourism. The method used is a simulation of planting sunflowers on an ex-mining area of 1 Ha, with a planting distance of 1 m, the number of sunflower plants is 8540. The research results show that with the sunflower garden concept by planting 8540 sunflowers, the Pb level that can be absorbed by the plants is 2.8310 kg.